New vulnerabilities upon Grain v0 Boolean function through fault injection analysis - Omar@Othman, Wan Zariman; Kamel Ariffin, Muhammad Rezal; Mohd. Jawi, Suhairi; Mahad, Zahari (CyberSecurity Malaysia Publication, 2021)
Algebraic attacks on stream cipher are very important in cryptography as well as in cryptanalysis. Generally, increasing degree of the equation will make an algebraic attack to the equation hardest. In conducting this analysis, we aim to decrease the degree of the targeted Boolean equation by constructing low degree annihilator equation(s). We adopt the Fault Injection Analysis (FIA) methodology to achieve our objectives. In this study, we found annihilator(s) through FIA (inject with value of one (1)) on Boolean function of selected stream ciphers. With the new injected Boolean functions developed, we proceed to utilize Hao’s method to find new annihilator(s). Then we established new annihilator(s) of Grain v0’s Boolean function. As a result, these newly identified annihilator(s) successfully reduce the complexity of the published Boolean function to guess the initial secret key. It also provides much needed information on the security and vulnerability of these selected stream cipher with respect to FIA.